Automatic solids feeder using fuzzy control: A tool for fed batch bioprocesses. (September 2020) - Borges, Alex Souza; Montano, Inti Doraci Cavalcanti; Sousa Junior, Ruy; Suarez, Carlos Alberto Galeano
Abstract: Processes in fed-batch using biomass as substrate can be more advantageous, presenting a higher productivity and a lower consumption of enzyme. However, in some cases, processes operating in fed batch may represent a problem in the way the substrate should be fed. In this article, a prototype for solids feeding is developed, which can implement different types of feeding profiles and is controlled through fuzzy logic. Tests considering different feeding profiles for two types of solid materials show that the use of a fuzzy controller provides better results when compared to the system using an On–Off control. The experimental validations of the feeding actions show that the system implementing the fuzzy controller is very effective and can be an alternative in enabling the processes of enzymatic hydrolysis in fed batch that use biomass as the main source for obtaining fermentable sugars. Highlights: A low-cost feeder allows transporting solids following different feeding profiles. A fuzzy logic controller provided better results when compared to On–Off control. The device is efficient and can be an alternative for fed-batch processes.